1996
DOI: 10.1006/anbo.1996.0013
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Macromolecular Composition of the Seed Coat of the Musaceae

Abstract: Mature seed coats of representatives of all three genera of Musaceae were analysed for macromolecular composition with various mass spectrometric techniques and compared with scanning electron microscopy and light microscopy in combination with histochemical techniques. Mass spectrometric techniques are more sensitive and more specific in identifying macromolecular compounds than histochemical methods. The macromolecular ' fingerprint ' of the seed coats of Musaceae showed unique components of aromatic phenols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
8

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 35 publications
2
41
0
8
Order By: Relevance
“…For phenolic polymers such as lignin, it has been shown that the products from THM are in better agreement with the molecular structure of lignin than those from conventional pyrolysis (Challinor, 1995(Challinor, , 2001). The phenolics and sugar product from the Juncus seed coats may relate to the lignin/cellulose complex observed in previous studies (van Bergen et al, 1994a, b;Graven et al, 1996Graven et al, , 1997van Bergen et al, 1997a, b;Stankiewicz et al, 1997;McCobb et al, 2001). …”
Section: Advantages Of Thm Over Conventional Pyrolysismentioning
confidence: 59%
“…For phenolic polymers such as lignin, it has been shown that the products from THM are in better agreement with the molecular structure of lignin than those from conventional pyrolysis (Challinor, 1995(Challinor, , 2001). The phenolics and sugar product from the Juncus seed coats may relate to the lignin/cellulose complex observed in previous studies (van Bergen et al, 1994a, b;Graven et al, 1996Graven et al, , 1997van Bergen et al, 1997a, b;Stankiewicz et al, 1997;McCobb et al, 2001). …”
Section: Advantages Of Thm Over Conventional Pyrolysismentioning
confidence: 59%
“…Fructobacillus was found to utilize the simple sugars fructose and glucose (previously determined to be utilized within the bee gut by the microbial community [34]), as well as the plant carbohydrate lignin. The utilization of lignin by Fructobacillus is particularly interesting; Fructobacillus is associated with pollen and flowers, and this complex plant carbohydrate is found in pollen collected by the honey bee (35)(36)(37)(38). Fructobacillus seems therefore well positioned to begin the breakdown of this important plant-derived food.…”
Section: Discussionmentioning
confidence: 99%
“…This condition was also reported in Xyris indica (Weinzieher 1914), X. pauciflora (Govindapa 1956), and Xyris recorded here in Xyris, but this conflicts with Carlquist's (1960) interpretation of the seed operculum in Achlyphila, Abolboda, and Orectanthe as chalazal, since a micropylar and chalazal seed operculum are doubtfully homologous. A micropylar seed operculum is recorded in several Commelinanae (Werker 1997), such as Eriocaulon (Govindapa and Ramaswamy 1980), Commelinaceae (Grootjen and Bouman 1981), Rapateaceae (Tiemann 1985;Venturelli and Bouman 1988), Typha (Werker 1997), and some Zingiberales (Grootjen 1983;Grootjen and Bouman 1988;Graven et al 1996).…”
Section: Floral Charactersmentioning
confidence: 99%